Risk Factors for Endothelial Decompensation after Penetrating Keratoplasty and Its Novel Therapeutic Strategies - Mengyuan Liu; Jing Hong (Journal of Ophthalmology)
Purpose. To review the risk factors and pathogenesis of endothelial decompensation after penetrating keratoplasty (PKP) and its novel therapeutic strategies. Methods. Literature review. Results. As the major cause of graft failure in PKP, endothelial decompensation of corneal allograft is considered an irreversible decrease in endothelial cell density and endothelial dysfunction. Various risk factors, including donor status and operative and recipient factors, have been found to be associated with this pathological process. Operative factors like graft size and recipient factors such as indications, glaucoma, or glaucoma surgery history are highly associated with the occurrence of endothelial decompensation, while others are still under investigation. Although the mechanism of these risk factors remains unclear, pathogenesis can be summarized as an acute and chronic loss of endothelium, and cell exchange between donor and recipient is at the core of chronic cell loss. Endothelial keratoplasty has been a useful alternative to repeat standard PKP in eyes with failed grafts. Descemet stripping automated endothelial keratoplasty (DSAEK) and Descemet’s membrane endothelial keratoplasty (DMEK) following failed PKP provide more rapid visual recovery and achieve better rates of graft survival than those of a second PKP. Conclusions. Any direct or indirect damage to the endothelium could cause the loss, morphological changes, and dysfunction of endothelial cells. Graft size, indications, and recipient glaucoma or glaucoma surgery history are risk factors for endothelial decompensation. DSAEK and DMEK are novel therapeutic strategies for failed PKP grafts and have potential superiorities compared with repeat PKP.